2018
DOI: 10.1097/mpg.0000000000001894
|View full text |Cite
|
Sign up to set email alerts
|

Reversal of Intestinal Failure in Children With Tufting Enteropathy Supported With Parenteral Nutrition at Home

Abstract: IED cases should have >92% chance of long-term survival and >50% chance of enteral autonomy by/in early adult life and 75% by 25 years. Even if PN dependent s/he can gain employment. Patients with IED managed on PN at home by an IF rehabilitation service should avoid intestinal transplant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 21 publications
3
17
0
Order By: Relevance
“…Our reports demonstrate the need to diagnose and treat PN-related complications to decrease the mortality of this disorder. We confirm previous observations that patients with TE can survive the first year(s) of life with breastfeeding or formula, despite the severe diarrhea, at the cost of stunted growth [5,22].…”
Section: Discussionsupporting
confidence: 90%
“…Our reports demonstrate the need to diagnose and treat PN-related complications to decrease the mortality of this disorder. We confirm previous observations that patients with TE can survive the first year(s) of life with breastfeeding or formula, despite the severe diarrhea, at the cost of stunted growth [5,22].…”
Section: Discussionsupporting
confidence: 90%
“…A longterm follow-up study of 13 tufting enteropathy patients showed a survival rate of more than 92% for those who relied on parenteral nutrition at home. 21 There was only one CGM case with SLC5A1 pathogenic variants in the Chinese population. 22 In this study, we examined the second case by panel sequencing.…”
Section: Patients With Watery Stoolmentioning
confidence: 98%
“…Currently there is no special treatment for CTE patients. Samuel Aquiline et al reported that 13 patients with CTE were treated with long-term family parenteral nutrition [9]. Finally, 12 patients survived for 8 to 30 years under long-term parenteral nutrition therapy and the proportion of weaning off parenteral nutrition gradually increased with age.…”
Section: Discussionmentioning
confidence: 99%